Assessing groundwater recharge zones through land use analysis for sustainable management of degraded catchments in Cokro Spring area of Klaten Regency, Indonesia - Riyanto, Dwi Siswo; Hendrayana, Heru; Erwindy, Jossi (Brawijaya University, 2025)
Sustainable groundwater availability depends on the optimal functioning of recharge zones, particularly in spring catchments that supply clean water. This study delineates groundwater recharge zones in the 81 km² Cokro Spring catchment, Klaten Regency, using an integrated approach combining Vertical Electrical Sounding (VES) geophysical data with a GIS-based Analytical Hierarchy Process (AHP). Eight parameters were analyzed: lithology, rainfall, land use land cover, soil, drainage density, groundwater level, slope, and topography. The resulting recharge map was validated using Receiver Operating Characteristic (ROC) analysis, incorporating both spring observation points and random data points. Results indicated three recharge categories: good (38%), dominated by lapilli tuff and fractured lava, moderate (35%), located in the western fine tuff zone, and poor (27%), in the central area characterized by massive lava and built-up land. Land use changes from 2019 to 2022 revealed increased settlements and reduced infiltration areas, which contributed to a decline in recharge potential. Groundwater levels from 2012 to 2025 decreased at all measurement points, likely driven by LULC changes and increased abstraction. The study demonstrated the effectiveness of the integrated VES-AHP-GIS approach for mapping recharge zones, providing a scientific basis for targeted groundwater conservation and sustainable resource planning in volcanic catchments.